Product-Focused Software Process Improvement 9th International Conference, PROFES 2008, Monte Porzio Catone, Italy, June 23-25, 2008, Proceedings - Jedlitschka, Andreas; Salo, Outi (Programming and Software Engineering, 2008)
This book constitutes the refereed proceedings of the 9th International Conference on Product Focused Software Process Improvement, PROFES 2008, held in Monte Porzio Catone, Italy, in June 2008. The 31 revised full papers presented together with 4 reports on workshops and tutorials and 3 keynote addresses were carefully reviewed and selected from 61 submissions. The papers address different development modes, roles in the value chain, stakeholders' viewpoints, collaborative development, as well as economic and quality aspects. The papers are organized in topical sections on quality and measurement, cost estimation, capability and maturity models, systems and software quality, software process improvement, lessons learned and best practices, and agile software development.